Early treatment with ambrisentan of mildly elevated mean pulmonary arterial pressure associated with systemic sclerosis: a randomized, controlled, double-blind, parallel group study (EDITA study) - Pan, Zixuan; Benjamin, Nicola; Eichstaedt, Christina; Blank, Norbert; Egenlauf, Benjamin; Fischer, Christine; Harutyunova, Satenik; Xanthouli, Panagiota; Lorenz, Hanns-Martin; Grünig, Ekkehard (Arthritis Research & Therapy, 2019)
The objective of this randomized, placebo-controlled, double-blind, parallel group, trial was to assess the effect of ambrisentan on mean pulmonary arterial pressure (mPAP) in patients with systemic sclerosis (SSc) and mildly elevated pulmonary hypertension (PH).